2021
DOI: 10.1080/21691401.2021.1968883
|View full text |Cite
|
Sign up to set email alerts
|

Effects of vancomycin linoleic acid nanoparticles on male reproductive indices of Sprague–Dawley rats

Abstract: The management of bacterial infections, especially trains of methicillin-resistant Staphylococcus aureus observe in health care settings, has markedly improved with the introduction of established drugs but using newer nano-based formulations. This study investigates the effects of vancomycin-linoleic acid nanoparticles on testicular tissue in an experimental animal model. Twenty-five adult male Sprague-Dawley rats maintained at the Animal House of the Biomedical Resources Unit were assigned to five groups nam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 51 publications
(51 reference statements)
0
4
0
Order By: Relevance
“… 28 However, these nanoparticles may cross the biological barriers to deposit in reproductive organs including testis, and thus impair semen quality by increasing inflammation, disrupting DNA structure, decreasing mitochondrial function, and promoting reactive oxygen species production and apoptosis. 39 , 40 , 41 To address this issue, Olana et al 18 analyzed the reactive oxygen metabolites, electrolytes, and interleukin‐6 in seminal plasma, but found no significant differences between the pre‐ and postvaccination stages of BNT162b2. Therefore, these seemingly rational claims had little or no scientific evidence from basic research, and were not supported by our pooled analysis of clinical data as well.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 28 However, these nanoparticles may cross the biological barriers to deposit in reproductive organs including testis, and thus impair semen quality by increasing inflammation, disrupting DNA structure, decreasing mitochondrial function, and promoting reactive oxygen species production and apoptosis. 39 , 40 , 41 To address this issue, Olana et al 18 analyzed the reactive oxygen metabolites, electrolytes, and interleukin‐6 in seminal plasma, but found no significant differences between the pre‐ and postvaccination stages of BNT162b2. Therefore, these seemingly rational claims had little or no scientific evidence from basic research, and were not supported by our pooled analysis of clinical data as well.…”
Section: Discussionmentioning
confidence: 99%
“…For example, both mRNA‐1273 and BNT162b2 are lipid nanoparticle‐formulated vaccines for COVID‐19 28 . However, these nanoparticles may cross the biological barriers to deposit in reproductive organs including testis, and thus impair semen quality by increasing inflammation, disrupting DNA structure, decreasing mitochondrial function, and promoting reactive oxygen species production and apoptosis 39–41 . To address this issue, Olana et al 18 analyzed the reactive oxygen metabolites, electrolytes, and interleukin‐6 in seminal plasma, but found no significant differences between the pre‐ and postvaccination stages of BNT162b2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several recent studies have reported that vancomycin may adversely affect the testes and cause apoptosis in some cases. [ 16 , 17 ]. It is still unclear how vancomycin causes testicular toxicity.…”
Section: Introductionmentioning
confidence: 99%